2019
DOI: 10.1093/jnen/nlz073
|View full text |Cite
|
Sign up to set email alerts
|

Tau Phosphorylation and Aggregation in the Developing Human Brain

Abstract: Tau hyperphosphorylation, mostly at serine (Ser) or threonine (Thr) residues, plays a key role in the pathogenesis of Alzheimer disease (AD) and other tauopathies. Rodent studies show similar hyperphosphorylation in the developing brain, which may be involved in regulating axonal growth and plasticity, but detailed human studies are lacking. Here, we examine tau phosphorylation by immunohistochemistry and immunoblotting in human fetal and adult autopsy brain tissue. Of the 20 cases with sufficient tissue prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(42 citation statements)
references
References 43 publications
2
40
0
Order By: Relevance
“…Nevertheless, these findings are consistent with previous work that suggest that the developing brain is more resilient to formation of toxic aggregates. 54 Similar to our data, in 6 patients who died within 3 days following severe TBI, the only TDP-43 pathology observed was an increase of pTDP-43 (S409/410) fragments in the nuclear fraction of the frontal cortex. 55 Interestingly, this study also showed a TBI-mediated exacerbation of TDP-43 pathology and cell death in a transgenic mouse expressing mutant TDP-43 (A315T), however, significant differences in TDP-43 pathologies between mouse and human samples were observed, thus necessitating the study of TBI in human cells.…”
Section: Discussionsupporting
confidence: 91%
“…Nevertheless, these findings are consistent with previous work that suggest that the developing brain is more resilient to formation of toxic aggregates. 54 Similar to our data, in 6 patients who died within 3 days following severe TBI, the only TDP-43 pathology observed was an increase of pTDP-43 (S409/410) fragments in the nuclear fraction of the frontal cortex. 55 Interestingly, this study also showed a TBI-mediated exacerbation of TDP-43 pathology and cell death in a transgenic mouse expressing mutant TDP-43 (A315T), however, significant differences in TDP-43 pathologies between mouse and human samples were observed, thus necessitating the study of TBI in human cells.…”
Section: Discussionsupporting
confidence: 91%
“…This may explain the presence of higher than expected levels of tau protein in immature regions by Western blotting compared with IHC. We did not attempt to quantify individual tau isoforms since it has been previously demonstrated on both the RNA and protein level that fetal tau consists exclusively of the shortest (0N3R) isoform, and the extensive phosphorylation of human fetal tau makes identifying individual isoforms on Western blotting difficult without phosphatase pretreatment (Hefti et al, 2018(Hefti et al, , 2019.…”
Section: Discussionmentioning
confidence: 99%
“…Tau also appears to play a role in glutamatergic signaling (Miller et al, 2014;Tracy and Gan, 2017), excitotoxicity (Liang et al, 2009), and epileptogenesis (Liu et al, 2017). Recently, it was demonstrated that human fetal tau has a predominantly short-isoform, hyperphosphorylated phenotype similar to that seen in AD (Hefti et al, 2018(Hefti et al, , 2019. It remains unclear, however, what cell types express tau in the developing human brain and when in development this occurs.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the levels of A40/A42 peptides in patient CSF and blood are implicated as disease biomarkers in the clinic 7,9 . Tau protein is a key component of microtubule assembly in axons and its function is regulated by phosphorylation on multiple residues including threonine 181 (Tau-pT181) 10 . Similar to A peptides, Tau protein and its pT181 form are also detectable in CSF and blood specimens; their levels are associated with disease progression 11 .…”
Section: Introductionmentioning
confidence: 99%